2021
DOI: 10.3390/mi12111311
|View full text |Cite
|
Sign up to set email alerts
|

Suspended Silicon Waveguide with Sub-Wavelength Grating Cladding for Optical MEMS in Mid-Infrared

Abstract: Mid-infrared (MIR) photonics are generating considerable interest because of the potential applications in spectroscopic sensing, thermal imaging, and remote sensing. Silicon photonics is believed to be a promising solution to realize MIR photonic integrated circuits (PICs). The past decade has seen a huge growth in MIR PIC building blocks. However, there is still a need for the development of MIR reconfigurable photonics to enable powerful on-chip optical systems and new functionalities. In this paper, we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…For comparison, the most relevant and recent works related to the conventional waveguide architectures belonging to different technology platforms were chosen. It can be observed that one of the popular approaches i.e., suspending 33 the core from the bulk results in considerable reduction of the bulk scattering losses. However, such a reduction has only been observed either at single or dual wavelength peaks (6.4 or 8.5) μm with approximate bandwidth up to 3 μm, using conventional waveguide architectures viz., Rib 48 and Ridge 31 type.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, the most relevant and recent works related to the conventional waveguide architectures belonging to different technology platforms were chosen. It can be observed that one of the popular approaches i.e., suspending 33 the core from the bulk results in considerable reduction of the bulk scattering losses. However, such a reduction has only been observed either at single or dual wavelength peaks (6.4 or 8.5) μm with approximate bandwidth up to 3 μm, using conventional waveguide architectures viz., Rib 48 and Ridge 31 type.…”
Section: Resultsmentioning
confidence: 99%
“…Such a possibility of high mode confinement within small volumes anticipates an ultra-strong nonlinear interaction for the purpose of the novel cavity-optomechanical (C-OM) devices and applications. Recently, technology platforms like silicon on insulator (SOI), 29 germanium on insulator (GOI), 14 indium phosphide (InP), 30 and Ge-rich SiGe 10 , 11 , 15 , 31 (silicon–germanium) with waveguide topologies like rib/ridge, 32 suspended, 33 , 34 and self-collimated virtual PxC have theoretically as well as experimentally, shown considerable improvement in the direction of achieving low-loss, multispectral on-chip MWIR transmission. Despite the flexibility that these waveguide platforms offer, the mandatory condition to have high refractive index contrast between core and cladding limits them to have minimum propagation losses at one or two wavelength peaks.…”
Section: Introductionmentioning
confidence: 99%
“…This enduring trend [2], together with the consequent evolution of massive low-cost and large-scale semiconductor and microelectronics technologies [3], also triggered the conception and manufacturing of micromechanical structures [4], paving the way to the birth and growth of Micro Electro-Mechanical Systems (MEMS) [5][6][7][8]. MEMS can be used as extremely miniaturized sensors, actuators, microgrippers [9][10][11], with different sorts of actuation [12][13][14], piezoelectric resonators [15,16], and wave-guides [17], to only name but a few. They share with microelectronic devices the same conceptual platform: processes, technologies, and facilities able to produce low-cost, large-volume fabrication steps [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A 150 nm wide Si wire is added in the middle of the comb structure to avoid the adhesion between adjacent free-standing beams. The grating period is chosen to satisfy the subwavelength condition, that is, Λ ≪ λ/(2 n eff ), where n eff is the waveguide mode effective index. , At the overlap region, the period is reduced to Λ/2, making our waveguide work in the deep-subwavelength regime, where reflection and diffraction effects are significantly suppressed. We define the duty cycle of ADMAC waveguide as W s /Λ, where W s is the width of the Si beam (Figure b).…”
mentioning
confidence: 99%